2013
DOI: 10.1016/j.compchemeng.2013.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a simple LNG process using sequential quadratic programming

Abstract: The efficiency of using sequential quadratic programming (SQP) for the optimization of a PRICO process for the production of liquefied natural gas (LNG) is demonstrated. Most of the returned objective values have been better, and the execution times much lower, than in most previously published work on similar optimization cases. The optimization runs discussed in this paper require around 5 minutes of execution time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(37 citation statements)
references
References 8 publications
0
34
0
3
Order By: Relevance
“…In our work we have found that using ordinary sequential quadratic programming (SQP) routines compared with a flowsheet simulator is feasible for simple processes as long as the optimization problem is formulated well [27]. For the same problems, convergence was much faster than other techniques reported in the literature [28,29,30].…”
Section: Evaluation Of Lng Processesmentioning
confidence: 89%
“…In our work we have found that using ordinary sequential quadratic programming (SQP) routines compared with a flowsheet simulator is feasible for simple processes as long as the optimization problem is formulated well [27]. For the same problems, convergence was much faster than other techniques reported in the literature [28,29,30].…”
Section: Evaluation Of Lng Processesmentioning
confidence: 89%
“…Hence, the focus has been on the PRICO LNG process, which is a relatively simple natural gas liquefaction process currently used in multiple plants world-wide (Hoffart and Price, 2014). Referring to Austbø et al (2014), the optimization of single cycle mixed refrigerant processes such as PRICO has previously been discussed in a number of works, and in a handful of these papers SQP techniques have been employed (Skaugen et al, 2010(Skaugen et al, , 2013Morin et al, 2011;Khan et al, 2012;Wahl et al, 2013). In our experience, the knowledge obtained in the study of relative simple processes like PRICO can also be applied for more complex processes.…”
Section: Introductionmentioning
confidence: 85%
“…The minimum of the temperature differences T n should be more than T h = 1.2 • C in all cases. This work is a continuation of the work in Wahl et al, 2013 where different values of T h was selected in order to compare with previous reported work. The largest value for T h has been used here.…”
Section: Optimization Scheme and Parameter Settingsmentioning
confidence: 97%
See 2 more Smart Citations